Holding Area Conceptual Design and Validation for Various Urban Air Mobility (UAM) Operations: A Case Study in Seoul–GyungIn Area - Youngjae Lee (MDPI AG, 2021)
As populations become concentrated in cities, traffic congestion increases, and urban air mobility (UAM) is being considered to face this problem. Accordingly, many institutions and companies around the world are developing UAM vehicles, building infrastructure, and researching flight operating systems. In this study, three holding area concepts have been designed that can control air traffic flows and avoid bad weather conditions when UAM vehicles are operating. These holding areas have been considered to allow UAM vehicles to fly by avoiding collisions with other UAM vehicles or structures such as buildings. After validating the turning radius analysis with existing aircraft, a case study on the holding area concept design for the Seoul–GyungIn area was performed to determine whether UAM vehicles can turn within a narrow radius. It was not possible for winged-type UAM vehicles to turn across the Han River at cruise speed. The holding area concepts and the turning procedure of this study can be used as guidelines when designing UAM corridors or UAM flight routes.